Facile preparation and characterization of poly(vinyl alcohol)/chitosan/graphene oxide biocomposite nanofibers - Liu, Yanan; Park, Mira; Shin, Hye Kyoung; Pant, Bishweshwar; Choi, Jawun; Park, Yong Wan; Lee, Jun Youb; Park, Soo-Jin; Kim, Hak-Yong (Journal of industrial and engineering chemistry (Seoul, Korea), 2014)
Poly(vinyl alcohol) (PVA)/chitosan (CS)/graphene oxide (GO) biocomposite nanofibers have been successfully prepared using aqueous solution by electrospinning. CS colloidal gel in 1% acetic acid can be changed to homogeneous solution by using electron beam irradiation (EBI). The uniform distributions of GO sheets in the nanofibers were investigated by field emission scanning electron microscopy (FESEM) and Raman spectroscopy. FESEM images illustrated that the spread single GO sheet embedding into nanofibers was formed via self-assembly of GO sheet and PVA/CS chains. And the average diameters of the biocomposite nanofibers decreased (200, 173, 160 and 123nm) with increasing the contents of GO (0.05, 0.2, 0.4 and 0.6wt%). Raman spectra verified the presence of GO in the biocomposite nanofibrous mats. The mechanical properties of as-prepared materials related with GO contents. It revealed that the highest tensile strength was 2.78MPa, which was 25% higher than that of neat PVA/CS nanofibers. Antibacterial test demonstrated that the addition of GO to PVA/CS nanofiber had great ability to increase inhibition zone till 8.6mm. Overall, these features of PVA/CS/GO nanofibers which were prepared by eco-friendly solvent can be a promising candidate material in tissue engineering, wound healing and drug delivery system.